2021
DOI: 10.1099/jmm.0.001350
|View full text |Cite
|
Sign up to set email alerts
|

Co-infection in critically ill patients with COVID-19: an observational cohort study from England

Abstract: Introduction. During previous viral pandemics, reported co-infection rates and implicated pathogens have varied. In the 1918 influenza pandemic, a large proportion of severe illness and death was complicated by bacterial co-infection, predominantly Streptococcus pneumoniae and Staphylococcus aureus . Gap … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
118
3
22

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(152 citation statements)
references
References 32 publications
9
118
3
22
Order By: Relevance
“…The incidence of healthcare-associated infections observed in this study was high compared to that reported in other studies, where the proportion of patients with secondary infection ranged between 5% and 30% [8][9][10][11], probably due to the variability of the diagnostic methods used as well as the treatments indicated. However, when these results are compared with those of studies that only evaluated patients hospitalized in the ICU, more similar results are observed, with incidences of in-hospital infections ranging between 40% and 58% [3,[12][13][14].…”
Section: Discussioncontrasting
confidence: 68%
“…The incidence of healthcare-associated infections observed in this study was high compared to that reported in other studies, where the proportion of patients with secondary infection ranged between 5% and 30% [8][9][10][11], probably due to the variability of the diagnostic methods used as well as the treatments indicated. However, when these results are compared with those of studies that only evaluated patients hospitalized in the ICU, more similar results are observed, with incidences of in-hospital infections ranging between 40% and 58% [3,[12][13][14].…”
Section: Discussioncontrasting
confidence: 68%
“…The prevalence of bacterial infections in COVID-19 patients admitted to the ICU has been reported in several studies. (Contou et al, 2020;Sharifipour et al, 2020;Baskaran et al, 2021). A recent systematic review and meta-analysis study evaluating co-infections among patients infected with COVID-19 performed by Langford et al reported that the rate of secondary bacterial infection is 14.3% (Langford et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…These pathogens have been associated mainly with hospital and ventilator-acquired pneumonia, particularly in the ICU cohorts. Among the gram-positive bacteria, coagulase-negative staphylococci as well as Enterococcus faecalis and Enterococcus faecium, following by S. aureus are the most common and mainly caused of BSIs [5][6][7].…”
Section: Introductionmentioning
confidence: 99%